PERANCANGAN STRUKTUR PLATFORM MEZZANINE UNTUK MESIN DEAERATOR DIGREASE PLANT - Mochamad Rizky Ramadhan (2021)
The mezzanine platform is a semi-permanent building which has an open design. In designing the construction of a mezzanine platform, 3 factors must be considered in a design, namely the beams, columns and bracing. The use of a mezzanine platform is used for the industrial sector, especially for the deaerator engine of the grease plant. In the process of designing the structure must get optimal results for its use and the response that occurs due to the load generated by the machine. In the analysis process using the finite element analysis method which aims to determine the strength of the structure.The results obtained where the stress shows that the mezzanine platform structure can withstand both the load generated by the liveload load with the FOS result being 11. The use of bracing affects the results obtained at the stress that occurs with a value of 2.275e+01 N/mm2 using ASTM A36 type material.